Implementasi Manajemen Pembiayaan dalam Meningkatkan Mutu Sekolah di SDIT Al Ishlah Cibinong Bogor - Wiwi Uswatiyah; Idham Kholid; Ismail Mustaqim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research in this thesis is based on the development of educational institutions today, so many are experiencing difficulties in developing and even no longer operating (closing), because they may not be able to survive in the current era of disruption. This is a problem that we often encounter in various regions, both rural and urban. Cost is also one of the influencing factors in the development and progress of schools or educational institutions and even affects the quality of students inside and outside school. In this study using qualitative methods, more precisely descriptive qualitative with a field research approach. The data obtained are in the form of written words, oral speech, forms of behavior that can be observed through interviews, observation and documentation. This specific finding description relates to the results of the study, compiled based on answers to questions in the research through interviews, documentation, and direct observations in the field. To describe financing management in an effort to improve the quality or quality of education at SDIT Al Ishlah Cibinong, Financing Management in Program Planning and Financing Management in Budget Management at SDIT Al Ishlah Cibinong